Analisis Faktor Risiko Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Sidorejo Kota Pagar Alam - Sugihartono Sugihartono; Pasiyan Rahmatullah; Nurjazuli Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Pneumonia is an infectious disease that remains a public health problem in Indonesia, the third cause of death in Indonesia after cardiovascular and tuberculosis. The high incidence of pneumonia mainly attacks in the age group of infants and children under five years old. In Pagar Alam city in 2009, there were 671 cases (IR = 4.9%). The purpose of this research was to determine the relationship between the house physical environment factor and individual faktor of children with pneumonia incidence in working area of Public Health Center, Sidorejo, Pagar Alam city. Method: This research was an observational study using case control design. While variables studied among other things are nutritional status, immunization status, history of breastfeeding, type of house flooring, proportion of bedroom ventilation, occupancy density, the presence of smoking family members, type of fuel used for cooking, the presence of family members suffering from respiratory tract infections. Subject of the research consists of two groups, namely case group and control group, each of which is consisting of 54 subjects. Data was collected by interview, observation, and measurement. Data analysis used analysis of univariate, bivariate with chi square, and multivariate with logistic regression, using a significant level of 0.05 (5%) to determine the risk of the independent variables on the dependent variables and the estimation of the risk (odds ratio) of the cause of pneumonia incidence on children under five years old. Result : The results of this research show that of the 9 risk factors studied, there are 3 variables with the risk of the incidence of pneumonia on children under five years old, namely a history of breastfeeding (OR = 8.958, 95% CI : 2.843 - 28.232), type of house floor (OR = 10.528, 95% CI : 2.612 - 42.441) and the presence of smoking family members (OR 8.888, 95% CI : 1.738 - 45.437). The variable at greatest risk of pneumonia incidence on children under five years old is type of house flooring. In conclusion, this research indicates that nutrition status, immunization status, breastfeeding history, type of house flooring, size of room ventilation, occupancy density, type of fuel used for cooking, and the presence of smoking family members are closely related to the incidence of pneumonia. Key words: pneumonia, children under five years old, physical environment of housing, Pagar Alam city